Correction: Variations of training load, monotony, and strain and dose-response relationships with maximal aerobic speed, maximal oxygen uptake, and isokinetic strength in professional soccer players. - Filipe Manuel Clemente; Cain Clark; Daniel Castillo; Hugo Sarmento; Pantelis Theodoros Nikolaidis; Thomas Rosemann; Beat Knechtle (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0225522.].